The Optimization of Catfish Smart Flavor Production by Biduri and Papain Enzymatic Hydrolysis - Yuli Witono; Ardiyan Dwi Masahid; Maria Belgis; Zuida Amalina Rizky (Food, Agriculture and Natural Resources - NETWORKS, 2021)
The consumption of Monosodium Glutamate with a large amount can lead to nerve cell damage to the brain so that natural ingredients substitute MSG is needed. In this research, we produced smart flavors from catfish through enzymatic hydrolysis by combining papain and biduri enzymes. The purpose of the study was to identify the influence of enzyme concentration and length of hydrolysis on the smart flavor characteristics and determine the best treatment to produce smart flavors. The parameters identified were color, yield, moisture content, dissolved proteins, degrees of hydrolysis, antioxidants, water binding ability, and emulsion stability. The results show the highest brightness are biduri and papain combination by 60:40 with one-hour hydrolysis. The highest dissolved protein is 50:50 combination with three-hour hydrolysis. In addition, antioxidant activity is marked in a combination of 50:50 with one-hour hydrolysis.